Komodifikasi Rumah Betang Tumbang Gagu sebagai Daya Tarik Pariwisata di Kabupaten Kota Waringin Timur, Kalimantan Tengah - Fatrisia Yulianie (UHN IGB Sugriwa Denpasar, 2018)
This article is about the commodification of the Betang Tumbang Gagu House in East Waringin Regency of Central Kalimantan as a tourist attraction. This article is aimed to discuss the philosophy of Betang house, the potential tourism of the Betang Tumbang GaguHouse, the factors commodifying, and the forms of commodification. The method applied in this study was the qualitative descriptive method in order to describe the relationship between phenomenon or phenomenon under study with a systematic, factual and accurate. Data collection is done by collecting and analyzing the data through the literature relating to issues to be investigated; such as the textbooks, scientific journals, and other legal sourcers. Descriptive interpretative methods were also used to analyze the data. The results of the analysis show that the Cultural Heritage of the Dayak tribe of Central Kalimantan Betang Tumbang Gagu is used as a cultural tourism attraction in the hope of preserving the history and culture of the past. It will be easier the passage of time and the increasing number of tourists who are on the way will lead to cultural degradation and authenticity (authenticity) of community culture. The existence of commodification in the utilization of cultural heritage of betang house as a tourist attraction give positive and negative impact. Cultural heritage is one part of the material aspects of human culture. Culture is not a knowledge that needs to beborne early on, sailors are also the identity of a nation that gives special features of other nations. The values of customs and traditions that have been entrenched as functioning as a unifying community, therefore it is necessary for the collaboration of all parties to maintain and preserve the cultural tourism attractions Betang Tumbang Gagu.